Differentiating experts' anticipatory skills in beach volleyball - Cañal-Bruland, R.; Mooren, M.; Savelsbergh, G. J. P. (Research Quarterly for Exercise and Sport, 2011)
In this study, we examined how perceptual-motor expertise and watching experience contribute to anticipating the outcome of opponents' attacking actions in beach volleyball. To this end, we invited 8 expert beach volleyball players, 8 expert coaches, 8 expert referees, and 8 control participants with no beach volleyball experience to watch videos of attack sequences that were occluded at three different times and to predict the outcome of these situations. Results showed that expert players and coaches (who were both perceptual-motor experts) outperformed the expert referees (who were watching experts but did not have the same motor expertise) and the control group in the latest occlusion condition (i.e., at spiker-ball contact). This finding suggests that perceptual-motor expertise may contribute to successful action anticipation in beach volleyball.